2013
DOI: 10.3389/fpsyg.2013.00508
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the representation of space and time while listening to music

Abstract: Music is known to alter people's ordinary experience of space and time. Not only does this challenge the concept of invariant space and time tacitly assumed in psychology but it may also help us understand how music works and how music can be understood as an embodied experience. Yet research about these alterations is in its infancy. This review is intended to delineate a future research agenda. We review experimental evidence and subjective reports of the influence of music on the representation of space and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
32
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 109 publications
(123 reference statements)
4
32
1
1
Order By: Relevance
“…Interrelations between emotional states and time judgments (Wittmann, 2009;Lambrechts et al, 2011;Schäfer et al, 2013;Wackermann et al, 2014;Droit-Volet et al, 2015), as well as between impulsivity traits, present and future orientation, and time perception (Baumann and Odum, 2012;Mueller et al, 2014;Wittmann et al, 2017), have been reported in previous studies. Higher arousal states and an impulsive present orientation lead to relative overestimations of duration.…”
Section: Waiting-room Study (Study 1)supporting
confidence: 54%
See 1 more Smart Citation
“…Interrelations between emotional states and time judgments (Wittmann, 2009;Lambrechts et al, 2011;Schäfer et al, 2013;Wackermann et al, 2014;Droit-Volet et al, 2015), as well as between impulsivity traits, present and future orientation, and time perception (Baumann and Odum, 2012;Mueller et al, 2014;Wittmann et al, 2017), have been reported in previous studies. Higher arousal states and an impulsive present orientation lead to relative overestimations of duration.…”
Section: Waiting-room Study (Study 1)supporting
confidence: 54%
“…This coincides with outcomes linked to comparable induction techniques, such as rhythm-induced trance, meditation, or listening to music. These lead to alterations in states of consciousness and mutually affect the senses of self, time, and space (Berkovich-Ohana et al, 2013;Schäfer et al, 2013;Wittmann, 2015).…”
Section: Perception Of Space and Selfmentioning
confidence: 99%
“…Since sound perception has survival value for humans partly because of its capacity to activate various emotion induction "mechanisms," or "information-processing devices at different levels of the brain, which utilize distinct types of information to guide future behavior," Juslin (2013) correctly points out that "the emotions represent an extension of the perceptual process that enables us to infer not only the identity and location of an object, but also its potential consequences or 'affordances'" (p. 240, emphasis added; see also Krueger, 2014). Indeed, as Krueger (2014) recently argues in "Affordances and the Musically Extended Mind," "musical affordances -via soliciting different forms of entrainment -enhance the functionality of various endogenous, emotion-granting regulative processes, drawing novel experiences out of us with an expanded complexity and phenomenal character" (p. 1; for further fascinating discussion on musical 4 Musicae Scientiae embodiment and affordances, see Harrison & Loui, 2014;Hutka, Bidelman, & Moreno, 2013;Keebler, Wiltshire, Smith, Fiore, & Bedwell, 2014;Maes, Leman, Palmer, & Wanderley, 2014;Reybrouck, 2001Reybrouck, , 2005Reybrouck, , 2012Schäfer, Fachner, & Smukalla, 2013).…”
mentioning
confidence: 99%
“…There are many studies that have demonstrated how music can change the way listeners experience space and time, including both experimental investigations (e.g., Bailey & Areni, 2006;Droit-Volet, Bigand, Ramos, & Bueno, 2010;Kellaris & Mantel, 1996;Lopez & Malhotra, 1991) and subjective reports collected with interviews (e.g., Fachner, 2011a;Gabrielsson, 2001Gabrielsson, , 2011Herbert, 2011Herbert, , 2013. Regarding the representation of time, music typically shortens the estimated length of temporal durations-an effect that is even more pronounced when the listener likes the music used in the study (see Schäfer, Fachner, & Smukalla, 2013, for an overview). In addition, it is known from subjective reports that musical experiences can cause feelings of timelessness or time dilation.…”
mentioning
confidence: 99%